2020
DOI: 10.3390/catal10111228
|View full text |Cite
|
Sign up to set email alerts
|

An Escape from Noble Metals for Generating Urethanes via Reductive Carbonylation of Nitroarenes over FeSe2/γ-Al2O3 †

Abstract: The reaction of FeCl3, SeO2, and Pyridine (Py) in the presence of methanol (MeOH) under CO pressure generates a black precipitate, which has been confirmed as ferric di-selenide, FeSe2 through different structure characterization methods. Furthermore, impregnation of 5 wt% of FeSe2 onto γ-Al2O3 exhibits better catalytic performance than FeSe2 due to the highly dispersed and smaller particle sizes ca. 200–300 nm. The reductive carbonylation of nitrobenzene (NB) was investigated over FeSe2/γ-Al2O3 as a heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…This reaction primarily utilizes homogeneous transition metal catalysts such as Pt, Rh, Ru, and Pd. However, recycling of these catalysts proves challenging. To address the separation issue, heterogeneous catalysts, including Fe–Cu metal selenides supported by cerium and γ-Al 2 O 3 , as well as Rh, Ru, and Pd complexes, , have been suggested, and various forms of such catalysts have been developed.…”
Section: Production Process Of Isocyanatementioning
confidence: 99%
“…This reaction primarily utilizes homogeneous transition metal catalysts such as Pt, Rh, Ru, and Pd. However, recycling of these catalysts proves challenging. To address the separation issue, heterogeneous catalysts, including Fe–Cu metal selenides supported by cerium and γ-Al 2 O 3 , as well as Rh, Ru, and Pd complexes, , have been suggested, and various forms of such catalysts have been developed.…”
Section: Production Process Of Isocyanatementioning
confidence: 99%
“…Despite the high catalytic activity of homogeneous catalysts, their recovery and recycling are a major concern for industrial applications. For effective separation of the homogeneous catalysts, various heterogeneous catalysts for the reductive carbonylation of nitroarenes have been developed by employing selenium, metal selenides of Fe and Cu supported on ceria and γ-Al 2 O 3 , and supported Rh, Ru, and Pd complexes. Unfortunately, the reactivity of these heterogeneous catalytic systems is lower relative to that of homogeneous Pd-based catalysts. For instance, Cenini et al attempted the use of Pd/Al 2 O 3 and Rh/Al 2 O 3 as heterogeneous catalytic systems for the reductive carbonylation of nitrobenzene (NB) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tran et al reported a CuSe 2 /CeO 2 as a novel heterogeneous catalyst for the reductive carbonylation of NB . This catalytic system showed >99% conversion with 96.4% MPC yield using an NB/CuSe 2 molar ratio of 44 under 8.3 MPa of CO at 160 °C in 4 h. In 2020, the same group reported a FeSe 2 system supported by γ-Al 2 O 3 as a heterogeneous catalyst revealing an improved TON of 85 . Although the recyclability was studied, a limited MPC was generated.…”
Section: Introductionmentioning
confidence: 99%